Investigating The Relationships Between Overall Tourist Satisfaction And Destination Attributes - A Survey Study Of Malaysian Travel And Tourist Industry. - Shahrivar, Rafat Beigpoor (2007)
The current study investigates the relationships between tourist satisfaction and different destination attributes in Malaysia. Review of related literature provided the scope of identifying basic aspects of tourist satisfaction, destination attributes and satisfaction measurement.